The meanings of Heaven and human nature ideology in Pre-Qin Confucianism for Moral Education in Malaysia - LIEW, Foot Yuen; YAM, Kah Kean (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2018)
Abstract In Malaysia, Moral Education is a subject that is compulsory for all non-Muslim students studying in government and private schools. While non-Muslim students study Moral Education, Muslim students are taught Islamic studies. The Malaysian Chinese students must accept the concepts and values of moral education in the national education system. However, they are also influenced by the moral ethics of Confucianism in their cultural values. Will there be any conflict with these different schools teaching of thoughts? This study explores the meanings of the ideology of Heaven and human nature of Confucianism and whether it is suitable for the teaching of Moral Education in Malaysia. This study will focus on the teaching by the three great masters of Pre-Qin Confucianism who are Confucius, Mencius, and Xunzi. Pre-Qin Confucianism retains the simple meaning and value of education as a cornerstone of Confucianism. It has far-reaching impact, in line with the purpose of this study. This study will first analyse the relationship between man and Heaven for the meaning of â€œBelief in Godâ€. Secondly, the attribute of nature and man in Confucianism will be discussed from the view of bioethics. Thirdly, this study will analyse the significance of the relationship between man and spirits of Pre-Qin Confucianism.